ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETERSEDIAAN PANGAN DI PROVINSI ACEH - Dewi Eka Nova; fajri Fajri; Romano Romano (Jurnal Bisnis Tani, 2017)
This study was meant to found out the affect of the harvest area, food price, and the availability of food from last year. The study conducted in Aceh Province, including dry grain commodity of North Aceh regency, corn commodity of South-East Aceh, soy commodity of Bireun, and cassava of Aceh Besar. This study is done by using secondary data. The analysis that used in this study was Ordinary Least Square (OLS) method and processed by SPSS v.22. The result of this study showed the determination coefficient value (R2), which the dry grains of North Aceh was 0.988, which means the variation that could define the availability of the dry grain before was 98.8%. Corns in South-East Aceh regency alone, had the determination coefficient value (R2) by 0.977, which means the availability of dry corns was 97.7%. The determination coefficient value (R2) ofsoy in Bireun regency was 0.917, which means the variation that could define the availability of the soy before was 91.7%. Meanwhile for the cassava, it had the determination coefficient value (R2) by 0.928, which means the variation that could define the availability of the cassava before was 92.8%. All of them simultaneously showed the harvest area, prices, were affected the availability of food in each study regency, and the availability of the year before did not affected the food availability.